Characterization of resistance patterns and genetic diversity of Escherichia coli isolated from geese in Northeastern China - Wanying Sun; Jianfei Chen; Xinyu Zhu; Yuan Xue (Poultry Science)
This study investigates the correlation between antimicrobial resistance and PFGE (Pulsed-Field Gel Electrophoresis) typing in Escherichia coli (E. coli) strains isolated from geese on four farms in Heilongjiang Province. A total of 109 isolates were subjected to antimicrobial susceptibility testing using the K-B paper diffusion method with 15 different antimicrobial agents. PFGE typing was then performed for further analysis. The results indicated that more than 70% of the isolates were resistant to ampicillin, amoxicillin, imipenem, tetracycline, and doxycycline. Observing the presence of multidrug resistance, with 92.66% of the strains exhibiting resistance to 6 to 9 drugs. Among the 12 most resistant isolates, eight distinct PFGE patterns were identified, with strain similarity coefficients ranging from 40% to 60%. These findings highlight the presence of complex drug-resistant genotypes among E. coli strains from geese across all four farms, each displaying varying levels of resistance.